DNA-programmed cell assembly: from cells, tissues to organoids - Chen, Zhenyi; Fu, Pan; Wang, Kaizhe (Frontiers in Bioengineering and Biotechnology, 2025)
The precise spatial organization of cells into functional tissues represents a fundamental challenge in biology and regenerative medicine. Conventional methods for directing cell assembly often lack the specificity, reproducibility, and dynamic control necessary to mimic native tissue architectures. This review explores the emerging use of DNA as a programmable and biocompatible strategy to engineer cell–cell interactions and construct hierarchically ordered tissue models. We first introduce the properties of various DNA toolbox and their strategies for cell modification and assembly. Importantly, we highlight the latest research advances in DNA-encoded cell spheroids, layered tissues, and organoids. Finally, we summarize current challenges and future directions in DNA-programmed assembly.